Development of extra-early provitamin A quality protein maize inbreds with resistance/tolerance to Striga hermonthica and soil nitrogen stress - Oyekale, S.A.; Badu-Apraku, Baffour; Adetimirin, Victor O.; Unachukwu, N.; Gedil, Melaku A (MDPI, 2021)
A hemiparasitic plant, Striga hermonthica (Del.) Benth and soil nitrogen stress are the key constraints to maize (Zea mays L.) productivity in sub-Saharan Africa, where commonly cultivated maize is the normal endosperm type that is deficient in provitamin A, tryptophan and lysine (PVATL). Seventy-six extra-early maize inbreds with provitamin A, tryptophan, and lysine qualities (TZEEIORQ) were developed to address these constraints, and four checks were assessed under Striga, low and high nitrogen conditions at three locations in Nigeria. The inbreds were further genotyped with two beta-carotene hydroxylase 1 (crtRB1) markers, and their seeds were quantified for provitamin A content. Significant (p < 0.01) genetic variations were observed for grain yield and other agronomic attributes of the inbreds under varying environmental conditions. Levels of PVATL for the inbreds ranged from 2.21–10.95 µg g−1, 0.04–0.08%, and 0.19–0.39%, respectively. Beta-carotene marker, crtRB1-3′TE, was polymorphic and grouped the inbreds into two. The marker was effective in identifying inbreds with moderate provitamin A content. Inbreds TZEEIORQ 5, TZEEIORQ 52, and TZEEIORQ 55 exhibited resistance to Striga, tolerance to nitrogen stress with moderate levels of PVATL and could be invaluable sources of favorable alleles for breeding nutritionally improved maize varieties with resistance/tolerance to Striga and soil nitrogen stress.